2016
DOI: 10.1186/s12284-016-0100-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Glycomic Characterization of Rice Chalky Grains Produced Under Moderate and High-temperature Conditions in Field System

Abstract: BackgroundGlobal climate models predict an increase in global mean temperature and a higher frequency of intense heat spikes during this century. Cereals such as rice (Oryza sativa L.) are more susceptible to heat stress, mainly during the gametogenesis and flowering stages. During periods of high temperatures, grain filling often causes serious damage to the grain quality of rice and, therefore, yield losses. While the genes encoding enzymes involved in carbohydrate metabolism of chalky grains have been estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 96 publications
(124 reference statements)
5
51
0
1
Order By: Relevance
“…These responses suggest that activation of starch degradation occurs along with the repression of starch biosynthesis in rice grains exposed to high temperature, and counteracts the deposition of starch in the maturing endosperm. Consistently, the traces of starch degradation were observed as small pits and holes on the surface of immature starch granules in the chalky part of grains ripened at high temperature ( Zakaria et al, 2002 ; Tsutsui et al, 2013 ; Kaneko et al, 2016 ).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…These responses suggest that activation of starch degradation occurs along with the repression of starch biosynthesis in rice grains exposed to high temperature, and counteracts the deposition of starch in the maturing endosperm. Consistently, the traces of starch degradation were observed as small pits and holes on the surface of immature starch granules in the chalky part of grains ripened at high temperature ( Zakaria et al, 2002 ; Tsutsui et al, 2013 ; Kaneko et al, 2016 ).…”
Section: Introductionsupporting
confidence: 54%
“…Therefore, it is unclear which α-amylases function to generate chalky grains at high temperatures. Moreover, whether the site where the chalkiness occurs in high temperature conditions is consistently associated with the expression pattern of α-amylase remains to be determined, although a previous proteomic study revealed that high temperature promoted the accumulation of α-amylase proteins, namely Amy3D and Amy3E, in mature grains ( Kaneko et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al (2017) used a notched-belly rice mutant, which has a translucent upper half and a chalky bottom half within a single grain, and detected 363 proteins that were expressed differently between the two parts. Kaneko et al (2016) demonstrated that some isoforms of a-amylase expression and soluble starch and glucose accumulation increased in chalky grains. The molecular mechanism explaning the relationship between heat and chalkiness is not fully understood, however.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BR-regulated ribosomal protein abundance may play an important role in orchestrate seed germination process. Besides seed germination, proteomic studies indicated that protein-synthesis-related proteins and ribosomal proteins also played important roles in forming rice chalky grains by modulating energy and metabolic pathways 50 51 . Recently, study also showed that BR involved in the energy metabolism regulation under stress conditions by inducing de novo protein synthesis 52 .…”
Section: Discussionmentioning
confidence: 99%